Determinants of farmers' biosecurity mindset: A social-ecological model using systems thinking - Pao, Hai-ni; Jackson, Elizabeth; Yang, Tsang-sung; Tsai, Jyan-syung; Sung, Watson H. T.; Pfeiffer, Dirk U. (Frontiers in Veterinary Science, 2022)
Commercial poultry is often farmed in high-density facilities, therefore, predisposing exposure to threats of infectious diseases. Studies suggest that it is likely that farmers have little motivation to practice on-farm biosecurity. In Taiwan, where high-density intensive poultry production is commonplace, unfortunately, several avian influenza outbreaks have occurred over the past decade despite the establishment of biosecurity procedures. To develop effective interventions, it is essential to understand the determinants of farmers’ biosecurity mindset through systems thinking. In this qualitative study, we directly explored the opinions of Taiwan’s chicken farmers, and a grounded theory analysis was performed. The study revealed that farmers allocate resources based on their justification for the optimisation of resource utilisation, and biosecurity is the most concerning challenge. Farmers focus on the economic aspects of their production systems, particularly when the implementation of biosecurity increases production costs, and there are multifaceted, complex barriers to implementing on-farm biosecurity. Although the participant farmers accepted to take major responsibility for disease management, paradoxically, some farmers blamed the practicality of government regulations and government employees' attitudes. Additionally, the farmers rejected the government’s intentions to ask farmers to take full responsibility for the outbreaks of avian influenza while some of them intended to ignore the perceived risks. Government interventions that were considered not directly related to biosecurity also negatively influenced farmers’ willingness to improve biosecurity. Using the interview results together with information in the scientific literature, we constructed a modified six-level social-ecological model to explain the complex influences of macro socio-economic conditions on farmers’ biosecurity mindset. The novelty of this research lies in its wider relevance to Taiwan’s chicken production industry in that it identifies it provides first-hand evidence-based knowledge to demonstrate a wide number of determinants of farmers’ biosecurity mindset. This social-ecological model highlights the importance of systems thinking for the development of behavioural interventions and allows adaptation to the local context. The findings of this study have relevance to Taiwan’s chicken production industry and potentially to similar systems in other countries in the wider region and should result in more effective animal health management at the farm level.